On-Chip Micro Mixer Driven by Elastic Wall with Virtual Actuator - Toshio Takayama; Makoto Kaneko; Chia-Hung Dylan Tsai (Micromachines, 2021)
In this paper, we propose an on-chip micromixer driven by an elastic wall with a virtual actuator. The on-chip micro mixer is composed of a circular chamber surrounded by a ring-shaped channel under isolation with an elastic wall. When vibrational pressure is put on the driving channel by an actuator, the volume of the circular chamber changes through the deformation of the elastic wall, as if there exists a virtual actuator near the wall. As a result, the liquid in the circular chamber is pushed out and pulled through the neck channel. This action creates a swirling flow in the circular chamber while maintaining isolation from the driving channel. Through experiments, we confirmed the swirling flow under an isolated environment using an air-based valve. The advantage of this approach is that the micromixer can be designed with a single layer having a simple mechanism.